Design and Implementation Of NAODV ETCP To Handle Jelly Fish Attack (International Journal of Engineering and Computer Science, 2017)
This paper modifies the existing TCP and AODV system to handle the jelly fish periodic dropping attack, the jellyfish packet reordering attack and the jelly fish delay variance attack. The proposed system modifies the AODV routing protocol and TCP to handle the jelly fish attack variants. The proposed system uses the E_TCP of the existing system along with the modified AODV routing to get the effective results. In the E_TCP protocol the buffer stores the sequence number and the acknowledgement time while in the NAODV_ETCP protocol the fr(forwarding ratio) is also stored in buffer. This paper analyzes the performance using PDR, E2Edelay and the throughput on the various scenario attacked by different types of jellyfish attack. The result analysis shows that the performance of NAODV_ETCP is better than the ETCP protocol